EFFECT OF THE USE OF Gracilaria sp. ON WATER QUALITY, PHYSIOLOGICAL AND GROWTH PERFORMANCE OF Holothuria scabra IN CULTURE TANK - Yuni Puji Hastuti; Moh. Burhanuddin Mahmud; Yuli Siti Fatma; Ridwan Affandi; Kukuh Nirmala (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2022)
Sea cucumber Holothuria scabra was reared on a small scale with the addition of seaweed Gracilaria sp. as a phytoremediation agent. This research aimed to determine the effect of Gracilaria sp. on water quality, physiological response, and growth performance of H. scabra. Ten individuals of H. scabra with an initial length of 5 ± 0.09 cm and an initial weight of 7.6 ± 0.2 g were reared in a culture tank (20 cm x 30 cm x 20 cm) with 15 cm of water depth. Gracilaria sp. was floated on the culture tank at three weight levels with three replicates, i.e., low (15 g); medium (30 g); and high seaweed density (45 g), with the control (0 g), during the 30-day rearing period. Results showed no significant difference in water temperature, dissolved oxygen (DO), salinity, and total ammonia nitrogen (TAN) between all treatments except for pH. There were no significant differences in ammonia and nitrite concentrations and significant differences in nitrate concentration and total organic matter (TOM) between all treatments and the control. On day 30, the application of Gracilaria sp. exhibited a lower nitrate concentration than the control. Gracilaria sp. maintained the water quality in the culture tank within a tolerable range for H. scabra. On the physiological response of H. scabra, high seaweed density exhibited the lowest blood cholesterol and glucose levels on day 30 and the highest specific growth rate (SGR) in weight (0.59 ± 0.2%) and length (1.16 ± 0.09%). The survival rate of H. scabra in all treatments reached 100%, suggesting the indoor cultivation system in this experiment did not negatively affect the growth of H. scabra.